A Comparative Study Analysing the Demographic and Economic Factors Affecting Life Expectancy among Developed and Developing Countries in Asia - Summoogum, Jena Parameswari; Fah, Benjamin Chan Yin (Asian Development Policy Review, 2016)
The two aims of the study are to analyse the demographic and economic factors affecting the life expectancy at birth among three developed and three developing countries in Asia, and to assess the gap between the developed and developing countries, based on the determinant factors of life expectancy. The sample consists of secondary data collected from 1990 to 2013. The demographic factors include the crude birth rate, crude death rate and population growth, while the economic factors consist of the Gross National Income (GNI) per capita, gross savings, total health expenditure and labour force participation rate. The factors affecting the life expectancy at birth were analysed by both the linear and logarithmic regression approaches. The logarithmic model was chosen to explain the objectives of the study due to the presence of anomalies in the linear model. The obtained results demonstrate the presence of a gap between the developed and developing countries. It is observed that the crude birth rate and the total health expenditures significantly affect the life expectancy in the three developed countries. However, the rise in the life expectancy in the developing countries cannot be explained by a specific regressor, and may occur due to country-based changes in the demographic or economic factors.